(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2008)
Eight almost complete medium-large sized (about 33 cm in s.l.) fossil fishes, belonging to the family Colobodontidae, are described from the Pelsonian (Anisian, Middle Triassic) of South China. Their cranial and postcranial features fit those of the genus Colobodus Agassiz, 1844 from the western Tethys. However, they are older than the previously known Colobodus species and, furthermore, they come far from the western Tethys, where most colobodontids have been found so far. The significance of our new findings, beyond the erection of a new species, lies in the fact that they are the first definite record of Colobodus outside the western Tethyan faunal province, and represent the oldest unequivocal colobodontids worldwide, as well as suggest that they could have originated in the East rather than the western Tethys, as previously thought.